The Prevalence, Risk Factors and Clinical Correlates of QTc Prolongation in Chinese Hospitalized Patients With Chronic Schizophrenia - Cao, Haiyan; Zhou, Yongjie; Li, Tao; Yao, Cong; Yang, Weiliang; Kong, Siying; Wang, Yanyan; Yu, Baoping; Jiao, Qingyan; Sun, Yun; Jia, Xiaoju; Wang, Yuting; et al. (Frontiers in Psychiatry, 2021)
Background: The QTc interval may be significantly prolonged in schizophrenia patients taking antipsychotics. Few studies have addressed antipsychotic-induced QTc prolongation (AIQTP) in Chinese patients. Objectives: This study was designed to evaluate the prevalence of AIQTP and its clinical correlates in Chinese patients with chronic schizophrenia. Methods: A total of 436 inpatients and 291 normal controls matched with age and sex were included. QTc prolongation was defined as 2 standard deviations (SD) above the mean value of normal controls. Positive and Negative Syndrome Scale (PANSS) and its five-factor model were used to evaluate psychopathological symptoms. Results: QTc interval was significantly longer in patients than in normal controls. The prevalence of AIQTP was 8.26%. More women than men displayed AIQTP. Compared with patients without AIQTP, the patients with AIQTP had significantly higher concrete/disorganized subscore, lower low density lipoprotein (LDL) and lower total protein (TP). Furthermore, binary logistic regression analysis showed that higher number of hospitalizations, higher concrete/disorganized subscore and lower LDL were risk factors for AIQTP. Correlation analysis indicated significant association between QTc interval and the following variables: sex, age, duration of illness, the number of hospitalizations, PANSS total score, fasting blood glucose (FPG). Finally, a multiple regression analysis showed that older age, antipsychotic polytherapy, higher PANSS total score, and lower LDL were risk factors for AIQTP. Among them, LDL seemed to be a protective factor for AIQTP. Conclusions: QTc interval was longer in schizophrenia patients than in normal controls. The prevalence of AIQTP was 8.26%. Some clinical characteristics were risk factors for AIQTP. And LDL seemed to be a protective factor for AIQTP.